2014
DOI: 10.1186/s13048-014-0097-z
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 activator (SRT1720) improves the follicle reserve and prolongs the ovarian lifespan of diet-induced obesity in female mice via activating SIRT1 and suppressing mTOR signaling

Abstract: BackgroundThe prevalence of obesity is increasing worldwide and significantly affects fertility and reproduction in both men and women. Our recent study has shown that excess body fat accelerates ovarian follicle development and follicle loss in rats. The aim of the present study is to explore the effect of SIRT1 activator SRT1720 on the reserve of ovarian follicle pool and ovarian lifespan of obese mice and the underlying mechanism associated with SIRT1 and mTOR signaling.MethodsAdult female Kunming mice (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 70 publications
7
61
0
Order By: Relevance
“…Data implicate mTOR up-regulation in the poor reproductive outcomes of overweight and obese patients, who are more likely to be infertile, have higher miscarriage rates, and poorer obstetric outcomes compared with normal-weight peers (32)(33)(34). Obese rats demonstrate accelerated ovarian follicle development and follicle loss and activation of the mTOR pathway (35), whereas SIRT1 activators, which suppress mTOR, improve the ovarian reserve (36). Caloric restriction in rats also down-regulates mTOR activity and preserves the ovarian reserve (37).…”
Section: Discussionmentioning
confidence: 99%
“…Data implicate mTOR up-regulation in the poor reproductive outcomes of overweight and obese patients, who are more likely to be infertile, have higher miscarriage rates, and poorer obstetric outcomes compared with normal-weight peers (32)(33)(34). Obese rats demonstrate accelerated ovarian follicle development and follicle loss and activation of the mTOR pathway (35), whereas SIRT1 activators, which suppress mTOR, improve the ovarian reserve (36). Caloric restriction in rats also down-regulates mTOR activity and preserves the ovarian reserve (37).…”
Section: Discussionmentioning
confidence: 99%
“…The dosage of SRT1720 (25 mg/kg/day) was chosen according to several research studies. Zhou et al suggested that a high dose of SRT1720 (50 mg/kg) could improve obesity induced by a high-fat diet in mice [47]. Minor et al indicated that either a high dose of SRT1720 (100 mg/kg) or a low dose of SRT1720 (30 mg/kg) could improve survival and longevity in obese mice [48].…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological activation of SIRT1 and SIRT6 prevented the age-dependent exhaustion of rat [11] and mice [12] follicle reserve.…”
Section: The Use Of Sirts To Study Control and Treat Ovarian Funmentioning
confidence: 99%
“…The mTOR blockers resveratrol and rapamycin can promote the accumulation of both SIRT1 and SIRT6 in ovarian cells [10,11]. On the other hand, SIRT1 can suppress mTOR activity within non-ovarian [8] and ovarian [12] cells. The data concerning interrelationships between mTOR and other SIRTs within the ovary have not yet been reported.…”
Section: The Use Of Mtor Regulators To Study Control and Treat Tmentioning
confidence: 99%
See 1 more Smart Citation